Lussazioni pure traumatiche coxofemorali - Gabellieri, P.; Castellani, I.; Gazzarri, F.; Dolfi, L.; Serpieri, S.; Pietrobono, D.; Bozzi, F. (Lo Scalpello - Journal, 2018)
PURE TRAUMATIC HIP DISLOCATION Pure hip dislocation represent a medical emergency that must be addressed immediately. Early diagnosis and timely treatment are the goals to be targeted. A delay in treatment or diagnosis, as evidenced by many authors, expose patients to complications such as arthrosis, necrosis of the femoral head, sciatic nerve injury and heterotopic calcifications. For these reasons, reduction of dislocation should be treated as soon as possible, if the patient’s conditions allow so.